Fragilidade em idosos hospitalizados determinada por marcadores inflamatórios: prevalência e fatores associados - ROZA, Liliane Beatriz (2014)
This study aimed to: analyze the prevalence of frailty and associated factors in elderly hospitalized in a hospital clinic in Uberaba, Minas Gerais and the following objectives: a) To characterize the hospitalized elderly patients according to sociodemographic aspects, related to behavioral and health; b) identify the prevalence of frailty and associated factors in through changes concurrency in inflammatory markers (C-reactive protein - CRP, leukocytes); c) estimating the cutoff time sitting pregresso hospitalization for the presence of fragility. Was characterized as observational, analytical type, cross-sectional surveys using blood collection and exploratory methods. The sample, selected at random and systematic way, consisted of 168 people aged ≥60 years, hospitalized in a hospital clinic in Uberaba, MG. Data collection was performed by blood collection in the analysis of plasma concentrations CRP and leukocytes, plus a questionnaire on individual interviews with sociodemographic information (sex, age, marital status, living arrangement and income); health (drug use, depressive symptoms, functional capacity), and behavioral (physical activity and time sitting). For the data analysis procedures were used descriptive and inferential statistics (Chi-square, Poisson Regression Models of Logistics and ROC curve). A greater proportion of men, dependent on ABVD and elderly with time ≥ 2014 minutes / day spent in the sitting position; the prevalence of frailty was 21.9%, predominantly in elderly males; and among the frail elderly, 40% presented dependence for carrying out ABVD, and 22.9% had sedentary behavior ≥ 240 minutes per day. Times> 257.1 and> 330 min / day were discriminating for the presence of weakness in males and females, respectively. The findings of this research are important to generate knowledge that subsidizes more effective action in the prevention of fragility.